Frequency of Left Main Anterior Wall Myocardial Infarction Presenting in Emergency Department of Tertiary Care Hospital Quetta - Shah, Sultan; Jalal Uddin; Fazal- Ur-Rehman; Muhmmad Hashim; Khan, Dost Mohammad; Ali, Hikmat; Sanaullah; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: Left main anterior wall myocardial infarction (AWMI) is one of the most severe forms of myocardial infarction (MI) due to the extensive myocardial territory involved. Timely diagnosis and treatment are critical to improving outcomes. Limited data exists on the prevalence and clinical characteristics of left main AWMI in resource-limited settings like Quetta. Objective: To assess the prevalence, demographic characteristics, risk factors, clinical presentation, and outcomes of left main AWMI among patients presenting to the emergency department of a tertiary care hospital in Quetta. Materials and Methods: A qualitative study was conducted on 120 patients diagnosed with left main AWMI. Data was collected through medical record reviews and in-depth interviews with patients and healthcare providers. Thematic analysis was used to identify recurring patterns related to demographics, risk factors, clinical symptoms, and treatment outcomes. Results: Most patients were male (70.8%) and aged ≥51 years (66.7%). Hypertension (91.7%), diabetes (70.8%), and smoking (54.2%) were common risk factors. Chest pain (100%) and shortness of breath (91.7%) were frequent symptoms. Thrombolysis (50%) and PCI (41.7%) were primary treatment modalities. Delayed presentations led to complications in 10% of cases. Conclusion: The study highlights the high burden of left main AWMI in Quetta, underscoring the importance of early detection, timely treatment, and improved healthcare infrastructure to enhance patient outcomes.